Comparison analyses of different models used to determine soil thermal conductivity and diffusivity at nimex site, Ibadan (2021)
Soil thermal properties regulate the separation of energy fluxes at the ground surface and they control the exchange of energy and mass between the soil and the atmosphere. The knowledge of these properties is needed in order to ascertain the heat flux distribution in the soil under steady and non-steady conditions. In this study, which lasted for 11 months starting from March 2006 to January 2007, we estimated soil thermal conductivity and thermal diffusivity at Nigeria Mesoscale Experiment (NIMEX) site, Ibadan using Johansen and Kersten models and Horton Numerical method. The aim of this work is to compare the results obtained from these models and to ascertain the level of agreement of the results. The result showed that for Johansen and Kersten models, the highest mean values of thermal conductivity and thermal diffusivity were obtained in the month of September 2006. For Johansen model the values are 4.18±0.08 Wm-1K-1 and 4.56±5.57*10-8m2s-1 for thermal conductivity and thermal diffusivity respectively and for Kersten model the thermal conductivity and thermal diffusivity values are 1.00±0.05 Wm-1K-1 and 1.07±0.22*10-8 m2s-1 respectively. This may be due to the observed increase in the soil moisture content within this month. The result obtained using Horton Numerical method showed that the highest mean thermal conductivity and thermal diffusivity values of 9.76 ±3.00 Wm-1K-1 and 10.70±3.30*10-8m2s-1 respectively were obtained in the month of December 2006 while the lowest mean values of -0.44 ±14.68 Wm-1K-1 for thermal conductivity and 0.10±12.70*10-8m2s-1 for thermal diffusivity were obtained in the month of September contrary to the results obtained with the first two models. The negative mean thermal conductivity value of -0.44 ±14.68 Wm-1K-1 obtained in the month of September 2006 using Horton Numerical method was probably due to the increase in soil moisture content which is as a result of increase in the amount of rainfall within this month that lowered the temperature at the near soil surfaces. Kersten model is in agreement with Johansen model but has low values making it unsuitable for very low soil moisture. Johansen model is likely the best model for estimating thermal conductivity and diffusivity.